Probabilistic seismic hazard analysis using a new ground motion intensity measure (2016)
The main objective of this work is to compute the probabilistic seismic hazard analysis for a region of Mexico using a new ground motion intensity measure which is based on the spectral acceleration and a parameter proxy of the spectral shape named Np. The motivation of using this new ground motion intensity measure is because recently it has demonstrated its potential in predicting the response of buildings subjected to earthquakes. In fact, it was demonstrated that intensity measures based on Np are more efficient compared with other parameter of the literature. It is important to mention that this is the first time that a probabilistic seismic hazard analysis is performed using this new intensity measurement.